SURVIVING CENTRALIZED STATE POWER CONTROL: THE CASE OF CHINESE QUEER WEB EPISODE 'ADDICTED - Wenyu Jiang,; Feng Long ,; Wan Aida Binti Wan Yahaya , (Journal of Islamic, Social, Economics and Development, 2024)
This case study examines the survival of the Chinese Queer community and their imagination in the face of high centralization and state power control on social media. The Chinese government's historical policies and cultural traditions have created a challenging environment for the acceptance of homosexuality and LGBT media content. The centralized power of the Chinese Communist Party (CCP) further exacerbates the control over media and limits freedom of expression. This study explores the impact of cultural traditions, the CCP's control over media, and the challenges faced by the Chinese Queer community in their pursuit of visibility and acceptance.